Defects signature in VOC characterization of thin-film solar cells. (15th May 2021) - Kumar, Atul; Ranjan, Pranay
Highlight: Abnormal features as observed in VOC dependence of thin film solar cells on temperature and illumination could be assigned to their generating causes. We performed simulation and observed unique features of high SRV, hole mobility, conduction band offset, resistance, Schottky barrier height and bulk defects on temperature and illumination dependent VOC curve. An individual secnario could be implicitly identified using combined VOC -temperature and VOC -illumination characterisation. Abstract: Abnormal features of VOC dependence on temperature and illumination are probed for p-n + -n ++ heterojunction family of solar cell devices. Thin-film solar cells of CIGS, CZTS, CdTe, SnS have p-n + -n ++ configuration. VOC plots associated with the device configuration/defect scenarios give identifiable features in a one-sided abrupt heterojunction. These features could be assigned to their generating causes akin to high surface recombination velocity, hole mobility, conduction band offset, resistance, Schottky barrier height and bulk defects. This analysis helps make a general prediction of defects or shortcomings present in the device by observing the VOC -temperature and VOC -illumination plots. An individual defect/shortcoming is introduced at a time in the simulated device model and a comparative study for temperature-VOC and illumination-VOC is performed. Features associated with various device shortcomings (high SRV, hole mobility, conduction band offset, resistance, Schottky barrier height, a nd bulk defects) are summarized. Finally based on the simulation of VOC -temperature and VOC -illumination plots characterization could diagnose and distinctly identify the defect present in the device.